2009
DOI: 10.1021/tx9003769
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interstrand Cross-Linking Activity of (1-Chloroethenyl)oxirane, a Metabolite of β-chloroprene

Abstract: With the goal of elucidating the molecular and cellular mechanisms of chloroprene toxicity, we examined the potential DNA cross-linking of the bifunctional chloroprene metabolite, (1-chloroethenyl)oxirane (CEO). We used denaturing polyacrylamide gel electrophoresis to monitor possible formation of interstrand cross-links by CEO within synthetic DNA duplexes. Our data suggest interstrand cross-linking at deoxyguanosine residues within 5′-GC and 5′-GGC sites, with the rate of cross-linking depending on pH (pH 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…In vivo, the formation of DNA and protein adducts has already been shown. Besides, due to its bifunctionality, epichlorohydrin can cause crosslinks between nucleophilic side chains of biological molecules, which illustrates the major genotoxic potential of this substance [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, the formation of DNA and protein adducts has already been shown. Besides, due to its bifunctionality, epichlorohydrin can cause crosslinks between nucleophilic side chains of biological molecules, which illustrates the major genotoxic potential of this substance [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The 30mer in this family has been shown previously to be efficiently cross-linked by DEB and related compounds [21]. Interstrand cross-links were purified via denaturing PAGE by excising the lowest mobility band, which was verified to contain dG-to-dG linkages at central distal deoxyguanosines via piperidine treatment and subsequent analysis of the fragments through denaturing PAGE (data not shown; for similar studies, see [9]).…”
Section: Resultsmentioning
confidence: 85%
“…13) [22]. Epichlorhydrin 47 as well as the related epibromohydrin 48 proved the crosslinking ability that was monitored by using denaturing polyacrylamide gel electrophoresis [21].…”
Section: Epoxide-containing Agentsmentioning
confidence: 97%
“…The R- The bifunctional chloroprene metabolite, (1-chloroethenyl) oxirane 49 also turned out to be an efficient cross-linking agent. In a recent study Wadugu et al suggested a possible mechanism for the formation of cross-link through oxirane 49 (Scheme 1) [22]. The nucleophilic attack on the protonated epoxide by the N 7 of a deoxyguanosine residue affords N7-(3-chloro-2-hydroxy-3-buten-1-yl)guanine.…”
Section: Epoxide-containing Agentsmentioning
confidence: 99%